Womanist and Black Feminist Responses to Tyler Perry’s Productions
XVIII, 277 p. 2 illus.
Keywords: Tyler Perry has made over half a billion dollars through the development of storylines about black women, black communities and black religion. Yet, a text that responds to his efforts from the perspective of these groups does not exist.